2010
DOI: 10.1577/m09-122.1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and Modeling of Electrofishing Capture Efficiency for Fishes in Wadeable Warmwater Streams

Abstract: Stream fish managers often use fish sample data to inform management decisions affecting fish populations. Fish sample data, however, can be biased by the same factors affecting fish populations. To minimize the effect of sample biases on decision making, biologists need information on the effectiveness of fish sampling methods. We evaluated single-pass backpack electrofishing and seining combined with electrofishing by following a dual-gear, mark-recapture approach in 61 blocknetted sample units within first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 42 publications
7
93
1
Order By: Relevance
“…Fish samples were limited to those collected by use of backpack and barge electrofishing gear (pulsed direct current) during a single upstream pass. Single-pass backpack electrofishing has been determined to be an effective and reliable approach for obtaining information on fish-assemblage structure, such as species richness, when based on consistent sampling protocols (Angermeier and Smogler, 1995;Bertrand and others, 2006;Price and Peterson, 2010; but see Meador and others, 2003). Fish-sampling data were screened for electrofishing sampling efficiency to improve sample consistency and to exclude sites where sampling conditions precluded capture of a representative cross section of the fish assemblage.…”
Section: Fish-assemblage Characteristicsmentioning
confidence: 99%
“…Fish samples were limited to those collected by use of backpack and barge electrofishing gear (pulsed direct current) during a single upstream pass. Single-pass backpack electrofishing has been determined to be an effective and reliable approach for obtaining information on fish-assemblage structure, such as species richness, when based on consistent sampling protocols (Angermeier and Smogler, 1995;Bertrand and others, 2006;Price and Peterson, 2010; but see Meador and others, 2003). Fish-sampling data were screened for electrofishing sampling efficiency to improve sample consistency and to exclude sites where sampling conditions precluded capture of a representative cross section of the fish assemblage.…”
Section: Fish-assemblage Characteristicsmentioning
confidence: 99%
“…Survey data for stream fishes typically comprise lists of species encountered at particular times and places, often with counts of individuals. However, count data typically lack explicit measures of capture efficiency, which may vary depending on habitat conditions during sampling and thus confound comparisons among counts made at different times (Yoccoz et al 2001;Price and Peterson 2010). In this study, we have used changes in observed species occurrences, rather than count data, to evaluate evidence of temporal faunal change.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneity in capture can vary among beach seine sampling methods, environmental conditions, and fish species and sizes (Murphy and Willis, 1996). Furthermore, failure to account for this sampling bias can introduce systematic error into the data, obfuscate important ecological relations, and negatively influence a manager's ability to make effective resource management decisions (Price and Peterson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Gear calibration methods require comparing the number of fish captured with beach seines to the known number or an unbiased estimate of the number of fish present in the sample area (Peterson and Paukert, 2009;Price and Peterson, 2010). A primary assumption of most fish abundance estimators (for example, removal or depletion methods; Parsley and others, 1989;Pierce and others, 1990) and all gear calibration methods is that the population is geographically closed while sampling (no immigration or emigration; Peterson and Paukert, 2009).…”
Section: Introductionmentioning
confidence: 99%